A COMPARATIVE STUDY OF ANTI-GASTRIC CANCER ACTIVITY BETWEEN AQUEOUS EXTRACT AND ETHANOL EXTRACT OF FOLIUM CORDYLINES FRUTICOSAE - Liu, Shaojun; Cao, Dongbo; Xiao, Zhiming; Liu, Fen; Wang, Xiaoyan; Zhao, Lian; Tian, Li; Shen, Shourong (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The active components in Folium Cordylines Fruticosae were extracted by heat reflux method. The solvents used were distilled water and ethanol. The effects of two types of extracts on gastric cancer cells were compared; dry extract yields were calculated, as well as the inhibition rates of gastric cancer MGC-803 cell proliferation and the colony cell counts. The micro-Kjeldahl method was used to measure the cell protein contents and to make a comprehensive comparison. The results showed that the MGC-803 cell inhibition rates of three different concentrations (32.5, 75 and 150 mg/ml) of ethanol extracts increased with the increase of concentration, which was 48.9% at a concentration of 150 mg/ml; aqueous extract of Folium Cordylines Fruticosae had very low inhibitory activity at a low concentration (32.5 mg/ml), which was remained at about 20%. After being affected by two types of extracts, cells had uneven sizes, with very low brightness, while the normal cells presented a uniform full form, with high definition.